PERISTIWA ISRA’ MI’RAJ DALAM AL-QUR’AN (STUDI TAFSIR SAINTIFIK: AL-JAWAHIR FI TAFSIR AL-QUR’AN AL-KARIM KARYA SYAIKH TANTAWI JAUHARI - Fadhlur Rahman Ahmad Shah; Agus Harir (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This research examines the Isra’ and Mi’raj event through the scientific exegesis Al-Jawahir fi Tafsir al-Qur’an al-Karim by Sheikh Tantawi Jauhari. The main problem addressed is how Tantawi Jauhari’s interpretation integrates scientific and spiritual aspects in understanding the event. This research employs a qualitative approach with library research, using the tafsir as the primary source and related literature as secondary sources. The findings reveal that Tantawi Jauhari emphasizes scientific dimensions such as night-time calculation, astronomy, and mathematics, while also highlighting spiritual values, particularly the obligation of prayer and divine wisdom. The study concludes that his approach provides a holistic understanding, viewing the Isra’ and Mi’raj as a miracle of Allah that bridges scientific knowledge with Islamic spirituality